Application of Management Theories for STEM Education The Case of SWOT Analysis - Hazzan, Orit (SpringerBriefs in Education,, 2018)
This work describes the application of management theories in STEM (Science, Technology, Engineering and Mathematics) education systems. Two chapters examine STEM education on the K-12 national level and one chapter focuses on the higher education institutional level. All chapters are based on comprehensive research. Thus, it will appeal to teachers, school principals, researchers, graduate students, government policymakers, and all practitioners who care about STEM education in schools, academia and government. In each chapter, SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis is used as a managerial strategic tool for the examination of factors that focus either on internal circumstances (strengths and weaknesses), or external ones (opportunities and threats).